2002
DOI: 10.1089/107632702760240580
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Covalent Grafting of RGD Peptides to the Surface of a Compliant Poly(Carbonate-Urea)Urethane Vascular Conduit versus Conventional Biological Coatings: Its Role in Enhancing Cellular Retention

Abstract: The aim of sodding prosthetic grafts with endothelial cells (EC) is to establish a functioning antithrombogenic monolayer of EC. Application of basement membrane proteins improves EC adherence on ePTFE grafts. Their addition to a biodurable compliant poly(carbonate-urea)urethane graft (CPU) was studied with respect to EC adherence. Preclot, fibronectin, gelatin, and collagen were coated onto CPU. RGD peptide, heparin, and both RGD and heparin were chemically bonded to CPU. Human umbilical vein EC (HUVEC) label… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 30 publications
1
58
0
Order By: Relevance
“…When cells were cultured on this surface, integrin binding was stimulated [26]. In an another field, Krijgsman et al [27] have shown that only covalent grafting of RGD peptides to the surface of a compliant poly(carbonate-urea) urethane vascular prothesis enhances endothelial cellular retention versus conventional biological coatings. In a term of differentiation, Ferris et al [28] have shown that rat calvarial osteoblast cultured 30 days on RGDC titanium alloys-coated surfaces produce significantly more alkaline phosphatase and osteocalcin mRNA at earlier time than on control surfaces in the presence of serum.…”
Section: Article In Pressmentioning
confidence: 99%
“…When cells were cultured on this surface, integrin binding was stimulated [26]. In an another field, Krijgsman et al [27] have shown that only covalent grafting of RGD peptides to the surface of a compliant poly(carbonate-urea) urethane vascular prothesis enhances endothelial cellular retention versus conventional biological coatings. In a term of differentiation, Ferris et al [28] have shown that rat calvarial osteoblast cultured 30 days on RGDC titanium alloys-coated surfaces produce significantly more alkaline phosphatase and osteocalcin mRNA at earlier time than on control surfaces in the presence of serum.…”
Section: Article In Pressmentioning
confidence: 99%
“…In vitro endothelialisation of ePTFE grafts has been shown to increase long-term patency rates compared to uncoated control grafts due to reduced platelet adhesion when placed in vivo. Extracellular matrix (ECM) molecule coatings such as fibronectin [11,12], or peptides derived from its sequences [15], collagen type I [16] and laminin have been found to support confluent layers of human endothelial cells in vitro. The effect of ECM precoating on the thrombomodulatory properties of graft materials has received less attention than their effect on endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, despite the development of many surface-based approaches for improving graft hemocompatibility [9,20-22,39-41], very few have yielded successful results in vivo , with one potential reason being lack of persistence of the surface modification. Although bulk incorporation of bioactive molecules directly into the polymer backbone could theoretically address stability issues, this approach has generally not been pursued, likely due to a combination of synthetic challenges and concern over loss of biomolecule availability or functionality upon copolymerization.…”
Section: Discussionmentioning
confidence: 99%
“…, modification with heparin or PEG) generally require additional modification to enable EC adhesion and growth [53]. For instance, polyurethanes that incorporate a thromboresistant functionality have also been modified with specific cell adhesion peptides [54-56] in order to render the material more favorable for EC adhesion and growth. However, these dual modifications greatly increase the complexity of the material fabrication, and are also complicated by the non-thrombogenic functionality competing for available surface space with the pro-EC adhesion sequence.…”
Section: Discussionmentioning
confidence: 99%